INTELLECTUAL CAPITAL, COMPANY’S PERFORMANCE AND GROWTH: AN EMPIRICAL STUDY AT BANKING COMPANIES IN INDONESIA - Eko Suyono Popy; Dian Indira Rina; Lesmana Wati (JAFFA, 2013)
In a very competitive business environment, the competitive advantage would be in the company favor if It can manage both capitals, i.e., physical and intellectual capitals. The objectives of this research are to examine the influence of intellectual capital  on  company’s  performance and  growth.  This  research  used  the  banking companies listed on Indonesia Stock Exchange for period 2008-2012. Applying the purposive sampling method, the total samples consists of 8 companies. By simple linier regression analysis, the result show that the intellectual capital has positive and significant influence on the company’s performance and growth.